2012
DOI: 10.1007/s13318-012-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketoprofen and indomethacin on methotrexate pharmacokinetics in mice plasma and tumor tissues

Abstract: Methotrexate (MTX) has been used in combination with nonsteroidal anti-inflammatory drugs in the treatment of inflammatory diseases as well as malignancies. Severe adverse effects with this combination may occur, usually resulting from inhibition of renal transporters. Solid Ehrlich carcinoma was experimentally induced by implantation of Ehrlich ascites Carcinoma cells subcutaneously into the thigh of mice, and after 30 days, mice were divided into three groups: Group I that served as control group received MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
3
7
0
1
Order By: Relevance
“…Several studies have shown that NSAIDs modulate expression of the ABC transporters [30][31][32][33][34][35] and possibly functions as substrates [30]. The present study supports these findings and suggests that carriers of polymorphisms that are associated with lower ABC transport activity benefit from the anti-inflammatory effect of the NSAIDs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies have shown that NSAIDs modulate expression of the ABC transporters [30][31][32][33][34][35] and possibly functions as substrates [30]. The present study supports these findings and suggests that carriers of polymorphisms that are associated with lower ABC transport activity benefit from the anti-inflammatory effect of the NSAIDs.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously found interaction between two polymorphisms in ABCB1 and red meat intake in relation to risk of CRC [29] which could be caused by a change in binding affinity or transport activity for PAHs and HCAs. Moreover, we found interaction between use of non-steroidal antiinflammatory drugs (NSAID) and an ABCB1 polymorphism which is in line with studies showing that several NSAIDs modulate expression of ABC transporters [30][31][32][33][34][35] or function as substrates for the ABC transporters [30]. In another study using the same study group as the present, we found interaction between several dietary factors and polymorphisms in genes encoding the cytokines interleukin 1-b (IL-1b) and IL-10 in relation to CRC risk [36].…”
Section: Introductionsupporting
confidence: 87%
“…Patients who take such medications daily should be provided with an alternative starting the day before HDMTX and continuing until methotrexate clearance. Studies in mice documented inhibition of renal tubule methotrexate transporters by indomethacin and ketoprofen, with reduced methotrexate elimination and prolonged elevated levels and toxicity [24]. …”
Section: Supportive Care Measuresmentioning
confidence: 99%
“…Pulmonary function testing or other screening is not warranted in patients with cancer, in whom methotrexate-induced pneumonitis is rare, unless pre-existing lung compromise or other risk factors warrant surveillance. Animal models, particularly rats, have been used to study toxicities of other therapeutics [24] and diseases, such as nonalcoholic steatohepatitis [25]. Rodent models have been used for pharmacokinetic modeling of methotrexate [26], exploring leucovorin rescue [27], and preclinical studies of investigational interventions to reduce toxicity (including pentoxifylline [28], amifostine [29], melatonin [30], and activators of peroxisome proliferator activator receptor a and g [31]).…”
Section: Other Toxicitiesmentioning
confidence: 99%
“…Esse tumor vem sendo utilizado como modelo experimental para várias pesquisas, incluindo: vigência de tratamento estrogênico e atividade imunológica (BAIOCHI et al, 1986); eficiência antitumoral na terapia fotodinâmica (BICALHO et al, 2012) e hipertermia ; estudos dos efeitos adversos graves do metotrexato na quimioterapia do câncer; atividade antineoplásica da bistirosina diaquaníquel (II) (KHANAM et al, 2008;ELMORSI, 2012); avaliação do crescimento tumoral sob o efeito de toxinas, extrato total e polissacarídeos isolados do cogumelo brasileiro Agaricus Blazei Murrill (ABM) (MADY, 2002;JUNIOR et al, 2007); ação de extratos vegetais (BREHMER, 2005;NASCIMENTO et al, 2005NASCIMENTO et al, , 2006; determinação de níveis enzimáticos e não enzimáticos em linfomas (SAROJA et al, 2012); inibição tumoral pelo compostos orgânicos isionatos ativos do amendoim (MOOS et al, 1971), disseminação linfática (DAGLI, 1989) e em estudos da eficiência da magnetohipertermia SADEGHIANI, 2008), entre outros.…”
Section: Tumor De Ehrlichunclassified